Five Basic Principles for Good Practices in Promoting Collaborative Learning: A Lesson from Students' Experiences - Zuraina, Ali (Universiti Malaysia Pahang, 2016)
Collaborative learning is a method that enables students to learn from their peers. In groups, members need to assist one another to facilitate their learning processes. At tertiary level, collaborative learning is essential as it teaches students to be independent learners. In the current study, interviews were conducted among four (4) students studying at tertiary level to identify their experiences in collaborative learning. Their learning experiences are then interpreted to principles of collaborative learning. Five principles serve as good practices were formulated from the data obtained. These are 'mutual understanding among group members', 'broad-mindedness in accepting views', 'readiness in admitting weak or wrong ideas', 'positive arguments' and 'encouraging discussion to promote critical points' Finally, recommendations can be made in that collaborative learning encourages students to state their opinions pertaining to an issue being discussed by analysing, synthesising and evaluating arguments made by group members.